ALTERATIONS IN PERIPHERAL BLOOD CD8+ T CELL SUBSETS IN PATIENTS WITH LUNG SARCOIDOSIS - Artem Arkad’evich Rubinstein; Igor Vladimirovich Kudryavtsev; Natalia Mihailovna Lazareva; Tatyana Viktorovna Akisheva; Olga Petrovna Baranova; Tatyana Pavlovna Ses’; Mikhail Mikhailovich Ilkovich; Areg Artemovich Totolian (Медицинская иммунология)
AbstractSarcoidosis is a systemic inflammatory disorder of unknown etiology characterized by tissue infiltration with macrophages and lymphocytes, including CD8+ T cells, and associated non-caseating granuloma formation. The aim of the study was to investigate various peripheral blood CD8+ T cells from patients with chronic respiratory sarcoidosis using markers of T cell maturation and ‘polarization’. Peripheral blood samples were collected from 34 patients with newly diagnosed chronic sarcoidosis of the respiratory organs with the background of a natural course of disease and without immunosuppressive therapy history. The diagnosis of pulmonary sarcoidosis was performed according to the standard criteria and was confirmed by histological examination for 94,12% of patients. Peripheral venous blood samples from healthy volunteers (n=40), matched by gender and age with patients with pulmonary sarcoidosis, was used as a control group. Multicolor flow cytometry revealed that patients with sarcoidosis had decreased levels of CD45RA+CD62L+ ‘naïve’ and CD45RA–CD62L+ central memory CD8+ T cells if compared with healthy controls, as well as the frequencies of ЕМ1 (CD45RA–CD62L–CD27+CD28+) и pre-effector type 1 (CD45RA+CD62L–CD27+CD28+) cells were also reduced. Next, to assess relevant ‘polarized’ CD8+ T cell subsets, we identified Tc1 (CCR6–CXCR3+), Tc2 (CCR6–CXCR3–), Tc17 (CCR6+CXCR3–), and double-positive Tc17.1 (CCR6+CXCR3+). We found that CXCR3-expressing CD8+ T cell subsets (Tc1 and Tc17.1) were significantly decreased both in relative and absolute numbers in patients with sarcoidosis if compared to healthy controls. Oppositely, Тс2 CD8+ T cell were significantly elevated. Furthermore, the relative numbers of Tc1 cells negatively correlated with serum ACE levels (r=–0,456 with р=0,010), while Тс2 levels positively correlated with serum ACE levels (r=0,623 with р<0,001). Thus, our results indicate that CD8+ T cells may play a role in the pathogenesis of sarcoidosis. More extensive clinical and immunological comparisons are required for further systematization of the obtained data.